Creation of An Appropriate Organizational and Economic Platform for the Development of Rural Business - Rustamova Faridakhan Anvarjonovna (Genius Publishing Group, 2023)
The world experience of socio-economic development of states and their territories, including villages, is a clear evidence and confirmation of the high importance and role of the small business sector in society in ensuring socio-economic development and sociopolitical stability. In almost all economically developed countries of the world, this sector represents the middle class, which is the basis for the sustainable development of the entire national economy and the economy at the local level, because it is the leading segment that contributes to the supply of goods and services to the market, the creation of new jobs and the reduction of unemployment.
Keywords: state policy; small business; rural entrepreneurship